2003
DOI: 10.1023/a:1024491219366
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neurotransmitters on the Chemokinesis and Chemotaxis of MDA-MB-468 Human Breast Carcinoma Cells

Abstract: Most patients suffering from breast carcinoma do not die due to the primary tumor but from the development of metastases. Active migration of cancer cells is a prerequisite for development of these metastases. We used time-lapse videomicroscopy and computer-assisted cell tracking of MDA-MB-468 human breast carcinoma cells, which were incorporated into a three-dimensional collagen matrix, in order to analyze the migratory activity of these cells in response to different neurotransmitters. Our results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
210
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(223 citation statements)
references
References 34 publications
9
210
0
4
Order By: Relevance
“…Another explanation for the association of beta-adrenergic signaling with cancer growth may be related to the immune system (Ben-Eliyahu et al, 2000). Norepinephrine and beta-AR signaling have strong stimulating effects on a number of cancer types, including cancers of the colon (Masur et al, 2001;, prostate (Palm et al, 2006), ovary (Sood et al, 2006;Thaker et al, 2006), breast (Drell et al, 2003) and pancreas .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation for the association of beta-adrenergic signaling with cancer growth may be related to the immune system (Ben-Eliyahu et al, 2000). Norepinephrine and beta-AR signaling have strong stimulating effects on a number of cancer types, including cancers of the colon (Masur et al, 2001;, prostate (Palm et al, 2006), ovary (Sood et al, 2006;Thaker et al, 2006), breast (Drell et al, 2003) and pancreas .…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, beta-adrenergic signaling stimulates cancer growth Cole and Sood, 2012). Preclinical studies have demonstrated that beta-adrenergic receptor (AR) signaling has strong stimulating effects in cancers of the colon (Masur et al, 2001;, prostate (Palm et al, 2006), ovary (Sood et al, 2006;Thaker et al, 2006), breast (Drell et al, 2003) and pancreas . Regarding the impact of beta-blockers (BBs) on cancer survival, a recent study showed that BBs reduce the development of metastasis and recurrence in non-metastatic breast cancer and improve cancer-specific survival (Powe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that stress hormones affect tumor cell motility and invasion. Drell and associates showed that multiple neurotransmitters such as substance P, dopamine, and norepinephrine had a stimulatory effect on the migration of breast cancer cells, but only norepinephrine had a chemotactic effect on breast cancer cells [41]. Similarly, other groups have demonstrated that norepinephrine was a potent inducer of colon cancer and prostate cancer cell migration, which could be inhibited by beta-blockers [30,42].…”
Section: Migration and Invasionmentioning
confidence: 99%
“…Substance P is a peptide in the neurokinin family, is located in both the central and peripheral nervous systems, and plays a role in stress reactions, anxiety, and depression [93,94]. Substance P promotes the migration of colon and breast carcinoma cell lines and is a chemoattractant for squamous cell lung cancer [40,41,95].…”
Section: Other Stress Mediatorsmentioning
confidence: 99%
“…Given that active migration and the ability to adhere to host tissues are critical determinants for metastasis development and that norepinephrine is a potent inducer of cancer cell migration [47],…”
Section: Discussionmentioning
confidence: 99%